(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
This article discusses the anatomical structure of the stomach, the glandular cells in its mucous membrane and the substances from which they are produced, the pancreas and its location, the sphincter of Oddi and its location, the effect of pancreatic juice on the motor and evacuation functions of the stomach.